Impact of the COVID-19 outbreak and the serum prevalence of SARS-CoV-2 antibodies in patients with inflammatory bowel disease treated with biologic drugs. Issue 3 (March 2021) - Bossa, Fabrizio; Carparelli, Sonia; Latiano, Anna; Palmieri, Orazio; Tavano, Francesca; Panza, Anna; Pastore, Maria; Marseglia, Antonio; D'Altilia, Mario; Latiano, Tiziana; Corritore, Giuseppe; Martino, Giuseppina; et al.
Abstract: Background: Patients receiving biologic therapies are at risk for viral infections. This study investigated the impact of the SARS-CoV-2 infection and the serum prevalence of SARS-CoV-2 antibodies in patients with inflammatory bowel disease (IBD) treated with biologic drugs. Methods: Information on demography, co-morbidities, clinical data regarding IBD, symptoms suggestive of the SARS-CoV-2 infection, close contacts with SARS-CoV-2 positive patients, hospitalization, and therapies administered for COVID-19 was collected for all patients who were being treated with biologic drugs. All patients underwent SARS-CoV-2 antibody testing. Results: Two hundred and fifty-nine patients (27 children) with a mean age of 42.2 ± 16.7 years (range 9 - 88) and a mean duration of disease of 13.4 ± 10 years (range 0.2 – 49) were enrolled. One hundred four patients (40.2%) had ulcerative colitis, and 155 (59.8%) had Crohn's disease. About the therapy: 62 patients were receiving infliximab, 89 adalimumab, 20 golimumab, 57 vedolizumab, 27 ustekinumab, 1 thalidomide, and 3 an experimental compound. The mean Charlson Comorbidity Index was 2. Thirty-two patients (12.3%) reported respiratory symptoms, and 2 of them were hospitalized (0.77%). Two patients resulted positive for IgG against SARS-CoV-2 (0.77%). Conclusions: In patients with IBD, treatment with biologic drug does not represent a risk factor for the SARS-CoV-2 infection.